Survey of management practices related to parasite control from ranched North American bison (Bison bison) in the southern United States - Kaylee R. Kipp; Joe L. Luksovsky; Christine M. Budke; Walter E. Cook; John S. Gilleard; Guilherme G. Verocai (Veterinary Parasitology, 2026)

Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Longitudinal surface-based morphometry reveals potential MRI biomarkers correlated with multidimensional brain health measures - Robyn A. Honea; Ankit Patel; William Guiler; Mark D’Esposito; Sandra Bond Chapman; Lori G. Cook; Jeffrey S. Spence (Brain Imaging and Behavior, 2026)

The use of pumping for hydraulic characterisation of dykes - Vair J. Pointon; Ilka Wallis; Daniel Partington; Paul Hedley; Peter G. Cook (Hydrogeology Journal, 2026)
Faults and dykes can control groundwater flow, acting as barriers, conduits, or composite conduit–barrier systems. This study investigates dyke hydraulic behaviour using numerical modelling of field-scale pumping tests at two sites in Western Australia, supported by a uniquely detailed hydrogeological dataset. At each site, pumping tests were conducted across dykes that impeded groundwater flow, as evidenced by asymmetric drawdown cones and delayed responses in observation wells situated across the dyke from the pumping well. High-resolution three-dimensional geological frameworks were developed, and transient groundwater flow models were calibrated using automated inversion with and without spatially variable parameterisation (pilot points) to represent heterogeneity. In all calibrated models, the horizontal hydraulic conductivity ( K h ) of dykes was estimated to be one to eight orders of magnitude lower than that of the surrounding formations. Representation of dykes in the model produced the largest improvement in model fit at both sites, reducing the parameterisation objective function by one to two orders of magnitude relative to model parameterisations without dykes. Further improvements in model fit were achieved by introducing heterogeneity into formations, dykes or both. Although including formation heterogeneity reduced posterior uncertainty in dyke K h estimates, posterior variance patterns revealed that, in some locations, calibration preferentially adjusted K h in formations adjacent to dykes rather than within the dykes. Dyke K h was tightly constrained in areas with available field data and observable drawdown. These findings demonstrate the importance of representing structural features when interpreting pumping-test responses in structurally complex groundwater systems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Microvertebrates from the Cliff End Bone Bed (Wealden, Lower Cretaceous), East Sussex, UK - Johnny Clavo Yamahuchi; Elizabeth Cook; Christopher J. Duffin; Peter A. Austen; Steven C. Sweetman; Pamela G. Gill; Claudia Hildebrandt; Tim Tomkinson; Michael J. Benton (Proceedings of the Geologists' Association, 2026)

Simultaneous detection of multiple viral pathogens in vacuumed dust from different building types - Austin Shamblin; Calissa Carlisle; Nicholas Nastasi; Genny M. Cook; Anthony C. Fries; Richard T. Agans; Seth Faith; Michael G. Sovic; Vanessa A. Varaljay; Karen C. Dannemiller (Building and Environment, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

Multi-temporal DEMs used to quantify the geomorphological impact of a late 20th century glacier re-advance at Schwarzberggletscher, Switzerland - Toby N. Tonkin; Nicholas G. Midgley; Simon J. Cook (Geomorphology, 2025)

Soil organic carbon better described by soil mineralogy and exchangeable cations than oak restoration in California rangelands - Stewart G. Wilson; Erika J. Foster; Fiona O’Neill; Ashely Banuelos; Avalon Cook; Keith Paustain; Yamina Pressler; Chelsea J. Carey (CATENA, 2025)

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

What temperature is best for the offshore farming of the Australasian snapper, Chrysophrys auratus ? A collective examination of growth, FCR, O 2 consumption and welfare - Selwyn P. Collins; Leonardo J. Magnoni; Denham G. Cook; Suzanne E. Black; Neill A. Herbert (New Zealand Journal of Marine and Freshwater Research, 2025)
The Australasian snapper ( Chrysophrys auratus ) is a candidate for offshore aquaculture in New Zealand. The culture of snapper requires knowledge of the best locations for farms and a key variable is water temperature. The oxygen‐ and capacity‐limited thermal tolerance (OCLTT) hypothesis suggests fish performance is optimised at the temperature that maximises absolute aerobic scope (AAS), whereas the ‘multiple performances–multiple optima’ (MPMO) idea, suggests AAS and other performance measures can have different optimal temperatures. Therefore, the applicability of the OCLTT for snapper was tested by holding juveniles at 15, 18, 21, or 24°C for two months and constructing thermal performance curves (TPCs) for specific growth rate (SGR), feed conversion ratio (FCR) and AAS, and an assessment of welfare indicators. We hypothesised that the OCLTT would apply with all TPCs optimised at 21°C. However, AAS showed no discernible peak with temperature (although lower at 15 than 18°C); SGR and FCR improved non‐linearly with temperature; and welfare indicators varied little with temperature. This lack of aerobic limitation and evidence of MPMO suggests snapper are amenable to culture across a significant temperature range with warmer water likely providing the highest levels of productivity with maintained welfare.

Molecular characterisation of a novel citrus-infecting emaravirus, citrus emaravirus 1 - R. Bester; C. Gill; J.H.J Breytenbach; C. Steyn; H.J. Maree; G. Cook (Archives of Virology, 2025)
The application of high-throughput sequencing (HTS) has accelerated the discovery of novel viruses and the genome sequencing of poorly characterised viruses in fruit crops, revealing a greater complexity of plant viromes than previously understood. Here, we report the identification and genomic characterisation of a novel emaravirus, tentatively named "citrus emaravirus 1" (CiEV1), from Citrus limon leaves collected in the North West Province of South Africa. HTS analysis identified contigs corresponding to the four conserved emaravirus genomic segments (RNA1-RNA4), each encoding characteristic proteins: RNA-dependent RNA polymerase, glycoprotein, nucleocapsid, and movement protein. Comparison of terminal sequences and phylogenetic analysis suggest placing CiEV1 within clade D of the genus Emaravirus (family Fimoviridae ). To date, no association with symptoms has been identified. This is the first report of an emaravirus detected in citrus, expanding the known host range of the genus and contributing to the growing evidence of viral diversity in citrus. Further investigation is required to determine the epidemiological significance of CiEV1 in citrus orchards.

Annotated checklist of Australian fossil non-marine aquatic molluscs - Winston F. Ponder; Alex G. Cook; Sherri Donaldson; Michael W. Klunzinger (Molluscan Research, 2025)

Food Resource Management, Not Food Security, Is Associated with Mediterranean Diet Adherence in Low-income Pregnant Patients - L. Bailey-Davis; K. Herb Neff; G. Wood; K. Brandt; A. Chang; A. Cook; S. Lutcher; K. Marshall; C. Seiler; L. Wright; A. Mackeen (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Highly mobile pelagic species co‐occur with fine‐scale ocean fronts - Alexandre Lhériau‐Nice; Denham G. Cook; Alice Della Penna (Limnology and Oceanography, 2025)
Coastal areas are an important source of food and a valuable tourism asset for communities, but also highly dynamic and heterogeneous environments. Understanding how marine species respond to the variability of their habitat is essential to sustainably manage coastal resources. Here we investigate the distribution of highly mobile marine species in relation to fine‐scale fronts ( a fronts for most species considered. Specifically blue mackerel, kahawai, and jack mackerel are most often found in regions of moderate to high chlorophyll a and characterized by strong spatial gradients in ocean color. On the other hand, seabirds and mammals collocated most often with higher chlorophyll a concentrations and lower gradients compared to the other species examined. These findings advance our understanding of how mobile marine species interact with fine‐scale coastal fronts, suggesting that these features and their variability need to be accounted explicitly for habitat modeling and effective management.

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Gondwanan relic or recent arrival? The biogeographic origins and systematics of Australian tarantulas - Ethan J. Briggs; Saoirse Foley; Lyn G. Cook (Molecular Phylogenetics and Evolution, 2025)

Role of benthic overwintering cyanobacteria seed stock on estuarine bloom dynamics - Ellen P. Preece; Timothy G. Otten; Janis Cooke; Katherine V. Cook (Harmful Algae, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

A quantitative approach to ranking management actions for an endangered pool-breeding amphibian - Aidan E. O'Brien; David G. Cook; Stacy Martinelli; Michael H. Fawcett; Christopher A. Searcy (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Differential endothelial cell cycle status in postnatal retinal vessels revealed using a novel PIP-FUCCI reporter and zonation analysis - Ziqing Liu; Natalie T. Tanke; Alexandra Neal; Tianji Yu; Tershona Branch; Arya Sharma; Jean G. Cook; Victoria L. Bautch (Angiogenesis, 2024)
Cell cycle regulation is critical to blood vessel formation and function, but how the endothelial cell cycle integrates with vascular regulation is not well-understood, and available dynamic cell cycle reporters do not precisely distinguish all cell cycle stage transitions in vivo. Here we characterized a recently developed improved cell cycle reporter (PIP-FUCCI) that precisely delineates S phase and the S/G2 transition. Live image analysis of primary endothelial cells revealed predicted temporal changes and well-defined stage transitions. A new inducible mouse cell cycle reporter allele was selectively expressed in postnatal retinal endothelial cells upon Cre-mediated activation and predicted endothelial cell cycle status. We developed a semi-automated zonation program to define endothelial cell cycle status in spatially defined and developmentally distinct retinal areas and found predicted cell cycle stage differences in arteries, veins, and remodeled and angiogenic capillaries. Surprisingly, the predicted dearth of S-phase proliferative tip cells relative to stalk cells at the vascular front was accompanied by an unexpected enrichment for endothelial tip and stalk cells in G2, suggesting G2 stalling as a contribution to tip-cell arrest and dynamics at the front. Thus, this improved reporter precisely defines endothelial cell cycle status in vivo and reveals novel G2 regulation that may contribute to unique aspects of blood vessel network expansion.

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Remote sensing of ice albedo using harmonized Landsat and Sentinel 2 datasets: validation - Shunan Feng; Joseph Mitchell Cook; Yukihiko Onuma; Kathrin Naegeli; Wenxia Tan; Alexandre Magno Anesio; Liane G. Benning; Martyn Tranter (International Journal of Remote Sensing, 2024)

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Exploiting the Greenland volcanic ash repository to date caldera-forming eruptions and widespread isochrons during the Holocene - Siwan M. Davies; Paul G. Albert; Anna J. Bourne; Sara Owen; Anders Svensson; Matthew S.M. Bolton; Eliza Cook; Britta J.L. Jensen; Gwydion Jones; Vera V. Ponomareva; Takehiko Suzuki (Quaternary Science Reviews, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Identifying the influence of episodic events on groundwater recharge in semi-arid environments using environmental tracers - M. Chmielarski; S. Dogramaci; P.G. Cook; G. Skrzypek; A. Jackson; M. Nelson Tredwell; J.L. McCallum (Journal of Hydrology, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Variation in functional composition of reef fishes along a tropical‐to‐temperate gradient - Charlotte G. Clay; James D. Reimer; Brigitte Sommer; Katie M. Cook; Masaru Mizuyama; Masami Obuchi; Iori Kawamura; Hiroki Kise; Maria Beger (Journal of Biogeography, 2024)
Aims Transformation of species and functional composition on subtropical reefs are ongoing due to poleward range shifts of some tropical species, with largely unknown consequences to ecosystem functioning. Trait‐based approaches are powerful tools to quantify such changes. Here, we evaluated changes in the trait composition of coral‐associated fish assemblages along a tropical‐to‐temperate environmental gradient of ca. 1400 km in southern Japan with abundance‐weighted trait expression to assess how trait composition changes with increasing latitude. Location Ryukyu Islands and southern Pacific coast of Japan. Taxon Reef fish. Methods We tested for shifts in trait space and functional redundancy, based on five morphological, life history and behavioural traits: maximum length, pelagic larval duration, trophic level, substrate preference and reproductive mode. Our trait database was coded with two approaches, first, by attributing a single value to each trait per species, and second, by fuzzy coding that allows more than one value per trait and hence considers some intraspecific trait variation. Results We found a reduction in specialist habitat traits (coral substrate preference, nesters and herbivores) and an increase in generalist traits (predators) with increasing latitude, along with a contraction in trait space from tropical‐to‐temperate reefs. Functional redundancy declined with increasing latitude. These trends were closely linked with latitudinal gradients in temperature, along with changes in other environmental factors such as turbidity and photosynthetically active radiation. Main Conclusion Functional turnover and contractions are thus likely due to the marginal conditions for coral‐associated fishes at higher latitudes, favouring generalist species, whereas increased resources at lower latitudes favour high redundancy and niche partitioning. Accounting for intraspecific trait variation indicated the same trends but highlighted increased functional vulnerability across all sites. We show that trait complexity in coral‐associated fish communities decreases from tropical‐to‐temperate reefs, highlighting the reduced functional scope that comes with marginal environmental conditions.

Short communication: Circadian variations and day-to-day variability of clinical signs used for the early diagnosis of pneumonia within and between calves - T. Lowie; J. Vandewalle; G. Hanley-Cook; B. Pardon; J. Bokma (Research in Veterinary Science, 2024)

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Associations of urinary metabolite concentrations of phthalates and phthalate replacements with body composition from mid-childhood to early adolescence - Lisa B. Rokoff; Shravanthi M. Seshasayee; Jenny L. Carwile; Sheryl L. Rifas-Shiman; Julianne Cook Botelho; Catherine M. Gordon; Russ Hauser; Tamarra James-Todd; Jessica G. Young; Clifford J. Rosen; Antonia M. Calafat; Emily Oken; et al. (Environmental Research, 2023)

Host phylogeny and ecological associations best explain Wolbachia host shifts in scale insects - Ehsan Sanaei; Gregory F. Albery; Yun Kit Yeoh; Yen‐Po Lin; Lyn G. Cook; Jan Engelstädter (Molecular Ecology, 2023)
Wolbachia are among the most prevalent and widespread endosymbiotic bacteria on Earth. Wolbachia 's success in infecting an enormous number of arthropod species is attributed to two features: the range of phenotypes they induce in their hosts, and their ability to switch between host species. Whilst much progress has been made in elucidating their induced phenotypes, our understanding of Wolbachia host‐shifting is still very limited: we lack answers to even fundamental questions concerning Wolbachia 's routes of transfer and the importance of factors influencing host shifts. Here, we investigate the diversity and host‐shift patterns of Wolbachia in scale insects, a group of arthropods with intimate associations with other insects that make them well suited to studying host shifts . Using Illumina multitarget amplicon sequencing of Wolbachia ‐infected scale insects and their direct associates we determined the identity of all Wolbachia strains. We then fitted a generalized additive mixed model to our data to estimate the influence of host phylogeny and the geographical distribution on Wolbachia strain sharing among scale insect species. The model predicts no significant contribution of host geography but strong effects of host phylogeny, with high rates of Wolbachia sharing among closely related species and a sudden drop‐off in sharing with increasing phylogenetic distance. We also detected the same Wolbachia strain in scale insects and several intimately associated species (ants, wasps and flies). This indicates putative host shifts and potential routes of transfers via these associates and highlights the importance of ecological connectivity in Wolbachia host‐shifting.

Total thermal neutron cross section measurements of hydrogen dense polymers from 0.0005–20 eV - D. Fritz; Y. Danon; K. Ramic; C.W. Chapman; J.M. Brown; G. Arbanas; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; P. Brain; A. Ney; et al. (Annals of Nuclear Energy, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Are we there yet? Management baselines and biodiversity indicators for the protection and restoration of subtidal bivalve shellfish habitats - Jose M. Fariñas-Franco; Robert L. Cook; Fiona R. Gell; Dan B. Harries; Natalie Hirst; Flora Kent; Rebecca MacPherson; Colin Moore; James M. Mair; Joanne S. Porter; William G. Sanderson (Science of The Total Environment, 2023)

ACPSEM position paper: the safety of magnetic resonance imaging linear accelerators - Nick Cook; Nikki Shelton; Stephen Gibson; Peter Barnes; Reza Alinaghi-Zadeh; Michael G. Jameson (Physical and Engineering Sciences in Medicine, 2023)
Magnetic Resonance Imaging linear-accelerator (MRI-linac) equipment has recently been introduced to multiple centres in Australia and New Zealand. MRI equipment creates hazards for staff, patients and others in the MR environment; these hazards must be well understood, and risks managed by a system of environmental controls, written procedures and a trained workforce. While MRI-linac hazards are similar to the diagnostic paradigm, the equipment, workforce and environment are sufficiently different that additional safety guidance is warranted. In 2019 the Australasian College of Physical Scientists and Engineers in Medicine (ACPSEM) formed the Magnetic Resonance Imaging Linear-Accelerator Working Group (MRILWG) to support the safe clinical introduction and optimal use of MR-guided radiation therapy treatment units. This Position Paper is intended to provide safety guidance and education for Medical Physicists and others planning for and working with MRI-linac technology. This document summarises MRI-linac hazards and describes particular effects which arise from the combination of strong magnetic fields with an external radiation treatment beam. This document also provides guidance on safety governance and training, and recommends a system of hazard management tailored to the MRI-linac environment, ancillary equipment, and workforce.

Total thermal neutron cross section measurements of yttrium hydride from 0.0005 - 3 eV - D. Fritz; Y. Danon; M. Rapp; T.H. Trumbull; M. Zerkle; J. Holmes; C.W. Chapman; G. Arbanas; J.M. Brown; K. Ramic; X. Hu; S. Singh; et al. (Annals of Nuclear Energy, 2023)

Mid- and long-chain leaf wax δ2H values in modern plants and lake sediments from mid-latitude North America - Ioana C. Stefanescu; Chandelle Macdonald; Craig S. Cook; David G. Williams; Bryan N. Shuman (Geochimica et Cosmochimica Acta, 2023)

Groundwater-level recovery following closure of open-pit mines - Caglar Bozan; Ilka Wallis; Peter G. Cook; Shawan Dogramaci (Hydrogeology Journal, 2022)
Open-pit mining has increased substantially over the past two decades. Many currently operating open-pit mines are facing the end of mine-life over the next few decades and, increasingly, focus is shifting towards mine-closure planning that provides evidence on available closure options under the given geological, hydro(geo)logical and climatic conditions. This study uses synthetic groundwater modelling to build basic process understanding of closure options and how these will determine the formation of pit lakes. This governs the long-term pit lake water quality and how postmining landscapes may be utilised. Simulations show that the recovery time of postmining groundwater levels increases with decreasing aquifer transmissivity. Final postmining water tables are predominantly controlled by the implemented mine closure options and climatic conditions. The most important decision is, thereby, whether to backfill the pit to above the water table or allow a pit lake to develop. Under moderately transmissive aquifer settings, backfilling of pits leads to rapidly rising groundwater levels within the first decade after mining, with water-table recoveries of above 70%. If mine voids remain unfilled, evaporation from the pit lake surface becomes a governing factor in determining whether the unfilled mine pit becomes a terminal sink for groundwater. Lake levels may remain subdued by several 10s of metres in arid to semiarid climates. If surplus surface water can be diverted into open pits, rapid filling can accelerate groundwater recovery of open pits in regions of low permeability. This is a less successful management option in transmissive aquifers.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Wolbachia in scale insects: a distinct pattern of infection frequencies and potential transfer routes via ant associates - Ehsan Sanaei; Yen‐Po Lin; Lyn G. Cook; Jan Engelstädter (Environmental Microbiology, 2022)
Summary Wolbachia is one of the most successful endosymbiotic bacteria of arthropods. Known as the ‘master of manipulation’, Wolbachia can induce a wide range of phenotypes in its host that can have far‐reaching ecological and evolutionary consequences and may be exploited for disease and pest control. However, our knowledge of Wolbachia' s distribution and the infection rate is unevenly distributed across arthropod groups such as scale insects. We fitted a distribution of within‐species prevalence of Wolbachia to our data and compared it to distributions fitted to an up‐to‐date dataset compiled from surveys across all arthropods. The estimated distribution parameters indicate a Wolbachia infection frequency of 43.6% (at a 10% prevalence threshold) in scale insects. Prevalence of Wolbachia in scale insects follows a distribution similar to exponential decline (most species are predicted to have low prevalence infections), in contrast to the U‐shaped distribution estimated for other taxa (most species have a very low or very high prevalence). We observed no significant associations between Wolbachia infection and scale insect traits. Finally, we screened for Wolbachia in scale insect's ecological associates. We found a positive correlation between Wolbachia infection in scale insects and their ant associates, pointing to a possible route of horizontal transfer of Wolbachia .

Understanding Verbosity: Funding Source and the Length of Consent Forms for Cancer Clinical Trials - Quyen Duong; Sumithra J. Mandrekar; Stacey J. Winham; Kathryn Cook; Aminah Jatoi; Jennifer G. Le-Rademacher (Journal of Cancer Education, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Corrigendum to: The global Microcystis interactome - K.V. Cook; C. Li; H. Cai; L.R. Krumholz; K.D. Hambright; H.W. Paerl; M.M. Steffen; A.E. Wilson; M.A. Burford; H.‐P. Grossart; D. P. Hamilton; H. Jiang; et al. (Limnology and Oceanography, 2021)

Conceptual uncertainties in groundwater and porewater fluxes estimated by radon and radium mass balances - Valentí Rodellas; Thomas C. Stieglitz; Joseph J. Tamborski; Pieter van Beek; Aladin Andrisoa; Peter G. Cook (Limnology and Oceanography, 2021)
Radium isotopes and radon are routinely used as tracers to quantify groundwater and porewater fluxes into coastal and freshwater systems. However, uncertainties associated with the determination of the tracer flux are often poorly addressed and often neglect all the potential errors associated with the conceptualization of the system (i.e., conceptual uncertainties). In this study, we assess the magnitude of some of the key uncertainties related to the determination of the radium and radon inputs supplied by groundwater and porewater fluxes into a waterbody (La Palme Lagoon, France). This uncertainty assessment is addressed through a single model ensemble approach, where a tracer mass balance is run multiple times with variable sets of assumptions and approaches for the key parameters determined through a sensitivity test. In particular, conceptual uncertainties linked to tracer concentration, diffusive fluxes, radon evasion to the atmosphere, and change of tracer inventory over time were considered. The magnitude of porewater fluxes is further constrained using a comparison of independent methods: (1) 224 Ra and (2) 222 Rn mass balances in overlying waters, (3) a model of 222 Rn deficit in sediments, and (4) a fluid‐salt numerical transport model. We demonstrate that conceptual uncertainties are commonly a major source of uncertainty on the estimation of groundwater or porewater fluxes and they need to be taken into account when using tracer mass balances. In the absence of a general framework for assessing these uncertainties, this study provides a practical approach to evaluate key uncertainties associated to radon and radium mass balances.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Genomic analysis of Caldalkalibacillus thermarum TA2.A1 reveals aerobic alkaliphilic metabolism and evolutionary hallmarks linking alkaliphilic bacteria and plant life - Samuel I. de Jong; Marcel A. van den Broek; Alexander Y. Merkel; Pilar de la Torre Cortes; Falk Kalamorz; Gregory M. Cook; Mark C. M. van Loosdrecht; Duncan G. G. McMillan (Extremophiles, 2020)
The aerobic thermoalkaliphile Caldalkalibacillus thermarum strain TA2.A1 is a member of a separate order of alkaliphilic bacteria closely related to the Bacillales order. Efforts to relate the genomic information of this evolutionary ancient organism to environmental adaptation have been thwarted by the inability to construct a complete genome. The existing draft genome is highly fragmented due to repetitive regions, and gaps between and over repetitive regions were unbridgeable. To address this, Oxford Nanopore Technology’s MinION allowed us to span these repeats through long reads, with over 6000-fold coverage. This resulted in a single 3.34 Mb circular chromosome. The profile of transporters and central metabolism gives insight into why the organism prefers glutamate over sucrose as carbon source. We propose that the deamination of glutamate allows alkalization of the immediate environment, an excellent example of how an extremophile modulates environmental conditions to suit its own requirements. Curiously, plant-like hallmark electron transfer enzymes and transporters are found throughout the genome, such as a cytochrome b 6 c 1 complex and a CO 2 -concentrating transporter. In addition, multiple self-splicing group II intron-encoded proteins closely aligning to those of a telomerase reverse transcriptase in Arabidopsis thaliana were revealed. Collectively, these features suggest an evolutionary relationship to plant life.

Seasonal asymmetry of equatorial East African rainfall projections: understanding differences between the response of the long rains and the short rains to increased greenhouse gases - Kerry H. Cook; Rory G. J. Fitzpatrick; Weiran Liu; Edward K. Vizy (Climate Dynamics, 2020)

Effect of blast-related mTBI on the working memory system: a resting state fMRI study - Kathleen F. Pagulayan; Eric C. Petrie; David G. Cook; Rebecca C. Hendrickson; Holly Rau; Melissa Reilly; Cindy Mayer; James S. Meabon; Murray A. Raskind; Elaine R. Peskind; Natalia Kleinhans (Brain Imaging and Behavior, 2020)

Investigating food limitations in wild fisheries: the attendance and growth responses of fish at an anthropogenic feeding station within a temperate estuary - Denham G. Cook; Peter Jaksons; Alistair Jerrett (Journal of Fish Biology, 2020)
To investigate whether wild fish populations are food limited, this study explored whether the provision of supplementary food had a positive effect on the abundance, condition and growth characteristics of estuarine fish assemblages in New Zealand. Feed (7690 kg) was delivered from an anthropogenic feeding station over a 60‐week period to a naturally occurring assemblage of wild fish. Yellow‐eyed mullet ( Aldrichetta forsteri ) of juvenile, sub‐adult and newly matured size classes were the dominant species actively foraging at the feeding station throughout its operation, whereas larger piscivorous species visited and foraged from the feed station over the summer period only. Other species were present in the wider area of Nelson Haven, but not at the feed station. No obvious changes in the condition factor of yellow‐eyed mullet were observed across the period of monitoring, and no changes in their catchability were detected – although marked seasonal variation in catch rates was observed. Results from tag‐recapture data identify that the length‐based growth rates of yellow‐eyed mullet recaptured near the feed station were higher than those of tagged individuals recaptured at a nearby comparison site, and were higher than the growth rates observed in natural populations of yellow‐eyed mullet in the wider region. Shifts in the median size of fish, as observed by acoustic observations, agreed with the tag‐recapture data. Although some of the results identified were not amenable to statistical analyses, the attendance of yellow‐eyed mullet at the feeding station, in combination with the improved estimates of growth by most of the techniques employed, indicates that yellow‐eyed mullet are food limited in their natural environment and that the growth performance of these fish can be positively affected by the increased availability of food.

Conjoint use of hydraulic head and groundwater age data to detect hydrogeologic barriers - Sarah K. Marshall; Peter G. Cook; Leonard F. Konikow; Craig T. Simmons; Shawan Dogramaci (Hydrogeology Journal, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Permian gastropods from the Ratburi Limestone, Khao Phrik, Central Thailand - Chatchalerm Ketwetsuriya; Alex G. Cook; Alexander Nützel (PalZ, 2020)

The effect of temperature and meal size on the aerobic scope and specific dynamic action of two temperate New Zealand finfish Chrysophrys auratus and Aldrichetta forsteri - Tomislav Flikac; Denham G. Cook; William Davison (Journal of Comparative Physiology B, 2020)

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

Case–control study of endogenous sex steroid hormones and risk of endometrial cancer - Christine M. Friedenreich; Jeroen W. G. Derksen; Thomas Speidel; Darren R. Brenner; Emily Heer; Kerry S. Courneya; Linda S. Cook (Cancer Causes & Control, 2020)

Orchid fleck virus associated with the first case of citrus leprosis-N in South Africa - Glynnis Cook; Wayne Kirkman; Rochelle Clase; Chanel Steyn; Elaine Basson; Paul H. Fourie; Sean D. Moore; Tim G. Grout; Elma Carstens; Vaughan Hattingh (European Journal of Plant Pathology, 2019)

Correction to: Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johanssen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Amyloid Precursor Protein Mediates Neuronal Protection from Rotenone Toxicity - Kathryn Cimdins; Hayley S. Waugh; Vicki Chrysostomou; M. Isabel G. Lopez Sanchez; Vanessa A. Johannsen; Mark J. Cook; Jonathan G. Crowston; Andrew F. Hill; James A. Duce; Ashley I. Bush; Ian A. Trounce (Molecular Neurobiology, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

Small Animal Multivariate Brain Analysis (SAMBA) – a High Throughput Pipeline with a Validation Framework - Robert J. Anderson; James J. Cook; Natalie Delpratt; John C. Nouls; Bin Gu; James O. McNamara; Brian B. Avants; G. Allan Johnson; Alexandra Badea (Neuroinformatics, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Protecting groundwater levels and ecosystems with simple management approaches - Saskia L. Noorduijn; Peter G. Cook; Craig T. Simmons; Stuart B. Richardson (Hydrogeology Journal, 2019)

Uncertainty assessment of spatial-scale groundwater recharge estimated from unsaturated flow modelling - Yueqing Xie; Russell Crosbie; Craig T. Simmons; Peter G. Cook; Lu Zhang (Hydrogeology Journal, 2019)

A synthesis to understand responses to capture stressors among fish discarded from commercial fisheries and options for mitigating their severity - Katrina V. Cook; Andrea J. Reid; David A. Patterson; Kendra A. Robinson; Jacqueline M. Chapman; Scott G. Hinch; Steven J. Cooke (Fish and Fisheries, 2019)
Discarding non‐target fish from commercial fisheries is controversial and has been a persistent concern for fisheries managers globally. Discard management strategies typically begin by understanding mortality rates among discarded fish, a challenging task given the dynamic, highly context‐specific nature of fisheries. An alternative is to develop our knowledge of how stressors operate by first understanding the causes of mortality that drive this context dependence. Particularly relevant to mitigation efforts is an understanding of how fish respond to the physical factors of fishing, such as the gear itself and methods of fishing and handling the gear. We provide a synthesis of how commercial fishing methods may influence discard mortality and outline means by which capture‐induced stress and injury can be mitigated for common commercial gear types, emphasizing method variants or alternatives during capture, handling, and release that could improve survival. This synthesis identifies exhaustion and injury as the most detrimental and ubiquitous stressors experienced by discarded fish, with few options for mitigating their effects. Trawls and hanging net fisheries are identified as the most harmful gears for by‐catch, characterized by high stress regardless of method variants and limited options for mitigation. Irrespective of gear type and type of stressor, minimizing durations of capture and handling and encouragement of good handling behaviour (e.g., during landing and sorting) will reduce the magnitude of stress and injury in fish, and ultimately increase survival.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Plantation performance of chestnut hybrids and progenitors on reclaimed Appalachian surface mines - Jeff G. Skousen; Kara Dallaire; Steffany Scagline-Mellor; Alexis Monteleone; Lindsay Wilson-Kokes; Jessica Joyce; Calene Thomas; Travis Keene; Curtis DeLong; Thomas Cook; Douglass F. Jacobs (New Forests, 2018)

Using biological–physical modelling for informing sea lice dispersal in Loch Linnhe, Scotland - N K G Salama; A C Dale; V V Ivanov; P F Cook; C C Pert; C M Collins; B Rabe (Journal of Fish Diseases, 2018)
Sea lice are a constraint on the sustainable growth of Scottish marine salmonid aquaculture. As part of an integrated pest management approach, farms coordinate procedures within spatial units. We present observations of copepodids being at relatively greater density than nauplii in upper waters, which informs the development of surface layer sea lice transmission modelling of Loch Linnhe, Scotland, for informing farm parasite management. A hydrodynamic model is coupled with a biological particle‐tracking model, with characteristics of plankton sea lice. Simulations are undertaken for May and October 2011–2013, forced by local wind data collected for those periods. Particles are continually released from positions representing farm locations, weighted by relative farm counts, over a 2‐week period and tracked for a further 5 days. A comparison is made between modelled relative concentrations against physical and biological surveys to provide confidence in model outputs. Connectivity between farm locations is determined in order to propose potential coordination areas. Generally, connectivity depends on flow patterns in the loch and decreases with increased farm separation. The connectivity indices are used to estimate the origins of the sea lice population composition at each site, which may influence medicinal regimens to avoid loss of efficacy.

Effects of group size on school structure and behaviour in yellow‐eyed mullet Aldrichetta forsteri - K. L. Middlemiss; D. G. Cook; A. R. Jerrett; W. Davison (Journal of Fish Biology, 2018)
Schooling behaviour in yellow‐eyed mullet Aldrichetta forsteri , a common fish species in New Zealand estuarine habitats, was investigated to identify interaction rules associated with group formation. Tank‐based three‐dimensional studies of three group sizes (15, 75 and 150 individuals) were carried out to measure the effects of these different group sizes on school structure during control, predation risk and foraging behavioural states. Increased group size positively correlated with nearest‐neighbour distance in control and foraging states. Swimming speed was the lowest in all three behavioural states in groups of 15 fish compared with 75 or 150. Immediate behavioural response following visual exposure to a simulated avian predator differed between groups resulting in loss of structure in larger groups. School shape was an oblong–oblate spheroid with a length, breadth and height ratio of 5:2:1 and the area of free space surrounding individual fish was spherical in shape with a high degree of spatial isotropy present in all size groups. These findings challenge traditional theories based on either local or global properties as key drivers of group structure. Instead, our results suggest that a more collaborative approach involving both group size and rules pertaining to nearest‐neighbour interactions affects collective behaviours in this species.

Coagulase-negative staphylococci are associated to the mild inflammatory pattern of healthcare-associated meningitis: a retrospective study - S. Couffin; D. Lobo; F. Cook; P. H. Jost; V. Bitot; R. Birnbaum; B. Nebbad; B. Aït-Mamar; W. Lahiani; M. Martin; G. Dhonneur; R. Mounier (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.

China’s urbanization in 1949–2015: Processes and driving forces - Chaolin Gu; Lingqian Hu; Ian G. Cook (Chinese Geographical Science, 2017)

Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability - Richard B. Sherley; Philna Botha; Les G. Underhill; Peter G. Ryan; Danie van Zyl; Andrew C. Cockcroft; Robert J.M. Crawford; Bruce M. Dyer; Timothée R. Cook (Conservation Biology, 2017)
Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant ( Phalacrocorax neglectus ), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster ( Jasus lalandii ). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.

Morphology and hydro-sensory role of superficial neuromasts in schooling behaviour of yellow-eyed mullet (Aldrichetta forsteri) - Karen L. Middlemiss; Denham G. Cook; Alistair R. Jerrett; William Davison (Journal of Comparative Physiology A, 2017)

Using basic metrics to analyze high-resolution temperature data in the subsurface - Margaret Shanafield; James L. McCallum; Peter G. Cook; Saskia Noorduijn (Hydrogeology Journal, 2017)

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

The structural history and mineralization controls of the world-class Geita Hill gold deposit, Geita Greenstone Belt, Tanzania - I. V. Sanislav; M. Brayshaw; S. L. Kolling; P. H. G. M. Dirks; Y. A. Cook; T. G. Blenkinsop (Mineralium Deposita, 2017)

Quantitative Biomonitoring in the Detroit River Using Elliptio complanata: Verification of Steady State Correction Factors and Temporal Trends of PCBs in Water Between 1998 and 2015 - Ken G. Drouillard; Mark Cook; Todd A. Leadley; Paul Drca; Ted Briggs; G. Douglas Haffner (Bulletin of Environmental Contamination and Toxicology, 2016)

The balance between nitrogen fixation and denitrification on vegetated and non‐vegetated intertidal sediments - Douglas G. Russell; F. Y. Warry; Perran L. M. Cook (Limnology and Oceanography, 2016)

Codivergence of the primary bacterial endosymbiont of psyllids versus host switches and replacement of their secondary bacterial endosymbionts - Aidan A. G. Hall; Jennifer L. Morrow; Caroline Fromont; Martin J. Steinbauer; Gary S. Taylor; Scott N. Johnson; James M. Cook; Markus Riegler (Environmental Microbiology, 2016)
Summary Coevolution between insects and bacterial endosymbionts contributes to the success of many insect lineages. For the first time, we tested for phylogenetic codivergence across multiple taxonomic scales, from within genera to superfamily between 36 psyllid species of seven recognised families (Hemiptera: Psylloidea), their exclusive primary endosymbiont Carsonella and more diverse secondary endosymbionts (S‐endosymbionts). Within Aphalaridae, we found that Carsonella and S‐endosymbionts were fixed in one Glycaspis and 12 Cardiaspina populations. The dominant S‐endosymbiont was Arsenophonus , while Sodalis was detected in one Cardiaspina species. We demonstrated vertical transmission for Carsonella and Arsenophonus in three Cardiaspina species. We found strong support for strict cospeciation and validated the informative content of Carsonella as extended host genome for inference of psyllid relationships. However, S‐endosymbiont and host phylogenies were incongruent, and displayed signs of host switching and endosymbiont replacement. The high incidence of Arsenophonus in psyllids and other plant sap‐feeding Hemiptera may be due to repeated host switching within this group. In two psyllid lineages, Arsenophonus and Sodalis genes exhibited accelerated evolutionary rates and AT‐biases characteristic of long‐term host associations. Together with strict vertical transmission and 100% prevalence within host populations, our results suggest an obligate, and not facultative, symbiosis between psyllids and some S‐endosymbionts.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Mortality risk from comorbidities independent of triple-negative breast cancer status: NCI-SEER-based cohort analysis - Helen Swede; Amna Sarwar; Anil Magge; Dejana Braithwaite; Linda S. Cook; David I. Gregorio; Beth A. Jones; Jessica R. Hoag; Lou Gonsalves; Andrew L. Salner; Kristen Zarfos; Biree Andemariam; et al. (Cancer Causes & Control, 2016)

Biofouling community composition across a range of environmental conditions and geographical locations suitable for floating marine renewable energy generation - Adrian K. Macleod; Michele S. Stanley; John G. Day; Elizabeth J. Cook (Biofouling, 2016)

Maize hybrids derived from GM positive and negative segregant inbreds are compositionally equivalent: any observed differences are associated with conventional backcrossing practices - Tyamagondlu V. Venkatesh; Erin Bell; Anna Bickel; Kevin Cook; Benjamin Alsop; Martijn van de Mortel; Ping Feng; Alan Willse; Tim Perez; Susan Riordan; George G. Harrigan (Transgenic Research, 2016)

Buffel grass and climate change: a framework for projecting invasive species distributions when data are scarce - Tara G. Martin; Helen Murphy; Adam Liedloff; Colette Thomas; Iadine Chadès; Garry Cook; Rod Fensham; John McIvor; Rieks D. van Klinken (Biological Invasions, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Combination of Pretreatment with White Rot Fungi and Modification of Primary and Secondary Cell Walls Improves Saccharification - Charis Cook; Fedra Francocci; Felice Cervone; Daniela Bellincampi; Paul G Bolwell; Simone Ferrari; Alessandra Devoto (BioEnergy Research, 2015)

Dual functions of NME1 in suppression of cell motility and enhancement of genomic stability in melanoma - David M. Kaetzel; Mary K. Leonard; Gemma S. Cook; Marian Novak; Stuart G. Jarrett; Xiuwei Yang; Alexey M. Belkin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Improving treatment strategies for patients with metastatic castrate resistant prostate cancer through personalized computational modeling - Jill Gallaher; Leah M. Cook; Shilpa Gupta; Arturo Araujo; Jasreman Dhillon; Jong Y. Park; Jacob G. Scott; Julio Pow-Sang; David Basanta; Conor C. Lynch (Clinical & Experimental Metastasis, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Hydroacoustic tracking of the endangered Atlantic whitefish (Coregonus huntsmani); comparative analysis from wild and hatchery reared populations - A. M. Cook; R. G. Bradford; P. Bentzen (Environmental Biology of Fishes, 2014)

Identifying hot spots of security vulnerability associated with climate change in Africa - Joshua W. Busby; Kerry H. Cook; Edward K. Vizy; Todd G. Smith; Mesfin Bekalo (Climatic Change, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Temperature effects on metabolic rate and cardiorespiratory physiology of the spiny rock lobster (Jasus edwardsii) during rest, emersion and recovery - Leonard G. Forgan; Nicholas P. L. Tuckey; Denham G. Cook; Alistair R. Jerrett (Journal of Comparative Physiology B, 2014)

Processes and Drivers of Nitrogen Removal in Stormwater Biofiltration - Emily G. I. Payne; Tim D. Fletcher; Perran L. M. Cook; Ana Deletic; Belinda E. Hatt (Critical Reviews in Environmental Science and Technology, 2014)

A multilocus evaluation of ermine ( Mustela erminea ) across the Holarctic, testing hypotheses of Pleistocene diversification in response to climate change - Natalie G. Dawson; Andrew G. Hope; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2014)
Aim We examined data for ermine ( M ustela erminea ) to test two sets of diversification hypotheses concerning the number and location of late P leistocene refugia, the timing and mode of diversification, and the evolutionary influence of insularization. Location Temperate and sub‐ A rctic N orthern H emisphere. Methods We used up to two mitochondrial and four nuclear loci from 237 specimens for statistical phylogeographical and demographic analyses. Coalescent species‐tree estimation used a Bayesian approach for clade divergence based on external mutation rate calibrations. Approximate Bayesian methods were used to assess population size, timing of divergence and gene flow. Results Limited structure coupled with evidence of population growth across broad regions, including previously ice‐covered areas, indicated expansion from multiple centres of differentiation, but high endemism along the N orth P acific coast ( NPC ). A bifurcating model of diversification with recent growth spanning three glacial cycles best explained the empirical data. Main conclusions A newly identified clade in N orth A merica indicated a fourth refugial area for ermine. The shallow coalescence of all extant ermine reflects a recent history of diversification overlying a deeper fossil record. Post‐glacial colonization has led to potential contact zones for multiple lineages in north‐western N orth A merica. A model of diversification of ermine accompanied by recent gene flow was marginally less well supported than a model of divergence of major clades in response to the most recent glacial cycles.

Characterising the distribution of near-shore submarine groundwater discharge along a coastline using 222 Rn and electrical conductivity - M. A. Short; S. Lamontagne; P. G. Cook; R. Cranswick (Australian Journal of Earth Sciences, 2014)

The relationship between glycine transporter 1 occupancy and the effects of the glycine transporter 1 inhibitor RG1678 or ORG25935 on object retrieval performance in scopolamine impaired rhesus monkey - Donnie Eddins; Terence G. Hamill; Vanita Puri; Christopher E. Cannon; Jeffrey A. Vivian; Sandra M. Sanabria-Bohórquez; Jacquelynn J. Cook; John A. Morrow; Fiona Thomson; Jason M. Uslaner (Psychopharmacology, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Convergent structure of multitrophic communities over three continents - Simon T. Segar; Rodrigo A. S. Pereira; Steve G. Compton; James M. Cook (Ecology Letters, 2013)
Astract Ecological theory predicts that communities using the same resources should have similar structure, but evolutionary constraints on colonisation and niche shifts may hamper such convergence. Multitrophic communities of wasps exploiting fig fruits, which first evolved about 75 MYA , do not show long‐term ‘inheritance’ of taxonomic (lineage) composition or species diversity. However, communities on three continents have converged ecologically in the presence and relative abundance of five insect guilds that we define. Some taxa fill the same niches in each community (phylogenetic niche conservatism). However, we show that overall convergence in ecological community structure depends also on a combination of niche shifts by resident lineages and local colonisations of figs by other insect lineages. Our study explores new ground, and develops new heuristic tools, in combining ecology and phylogeny to address patterns in the complex multitrophic communities of insect on plants, which comprise a large part of terrestrial biodiversity.

Upper thermal tolerances of key taxonomic groups of stream invertebrates - Barbara A. Stewart; Paul G. Close; Peter A. Cook; Peter M. Davies (Hydrobiologia, 2013)

Colorful displays signal male quality in a tropical anole lizard - Ellee G. Cook; Troy G. Murphy; Michele A. Johnson (The Science of Nature, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Rejoinder: challenge and opportunity in the study of ungulate migration amid environmental change - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)

Animal migration amid shifting patterns of phenology and predation: lessons from a Yellowstone elk herd - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)
Migration is a striking behavioral strategy by which many animals enhance resource acquisition while reducing predation risk. Historically, the demographic benefits of such movements made migration common, but in many taxa the phenomenon is considered globally threatened. Here we describe a long‐term decline in the productivity of elk ( Cervus elaphus ) that migrate through intact wilderness areas to protected summer ranges inside Yellowstone National Park, USA. We attribute this decline to a long‐term reduction in the demographic benefits that ungulates typically gain from migration. Among migratory elk, we observed a 21‐year, 70% reduction in recruitment and a 4‐year, 19% depression in their pregnancy rate largely caused by infrequent reproduction of females that were young or lactating. In contrast, among resident elk, we have recently observed increasing recruitment and a high rate of pregnancy. Landscape‐level changes in habitat quality and predation appear to be responsible for the declining productivity of Yellowstone migrants. From 1989 to 2009, migratory elk experienced an increasing rate and shorter duration of green‐up coincident with warmer spring–summer temperatures and reduced spring precipitation, also consistent with observations of an unusually severe drought in the region. Migrants are also now exposed to four times as many grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) as resident elk. Both of these restored predators consume migratory elk calves at high rates in the Yellowstone wilderness but are maintained at low densities via lethal management and human disturbance in the year‐round habitats of resident elk. Our findings suggest that large‐carnivore recovery and drought, operating simultaneously along an elevation gradient, have disproportionately influenced the demography of migratory elk. Many migratory animals travel large geographic distances between their seasonal ranges. Changes in land use and climate that disparately influence such seasonal ranges may alter the ecological basis of migratory behavior, representing an important challenge for, and a powerful lens into, the ecology and conservation of migratory taxa.

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Temporal, spatial and ecological dynamics of speciation among amphi‐ B eringian small mammals - Andrew G. Hope; Naoki Takebayashi; Kurt E. Galbreath; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2013)
Aim Quaternary climate cycles played an important role in promoting diversification across the N orthern H emisphere, although details of the mechanisms driving evolutionary change are still poorly resolved. In a comparative phylogeographical framework, we investigate temporal, spatial and ecological components of evolution within a suite of H olarctic small mammals. We test a hypothesis of simultaneous divergence among multiple taxon pairs, investigating time to coalescence and demographic change for each taxon in response to a combination of climate and geography. Location Beringia, the nexus of the northern continents. Methods We used approximate B ayesian computation methods to test for simultaneous divergence among eight pairs of taxa, using cytochrome b gene sequences. We calculated coalescence times for eastern and western components of each pair and for the combined pairs, and relate dates to Q uaternary climatic periodicity and combinations of environmental events and physical barriers. Population growth and expansion statistics were used to test evolutionary responses among taxa, including range shifts, persistence or periodic extirpation. Species distribution models ( SDM s) for each taxon were used to predict their geographical ranges during the present interglacial, L ast G lacial M aximum and previous interglacial. Results Multiple divergence events across B eringia were primarily coincident with extreme glacial cycles of the late Q uaternary. Structure within B eringia is spatially consistent with at least three environmental barriers arising at different times: the K olyma U plands, B ering S trait and portions of the B ering I sthmus. Levels of divergence varied substantially, indicating evolutionary processes spanning deep and shallow time‐scales. The different demographics among taxa reflect their distinct ecological responses. SDM s predicted regional distributional changes through time and different spatial responses among taxa. Main conclusions Beringia predominantly constituted a dispersal corridor during the early Q uaternary and a major centre of endemism in the late Q uaternary. Coincident with severe glacial cycles, small mammal species were ‘caught’ in B eringia and diversified over multiple climatic phases. Relative genetic differentiation across B eringia appears to be related to ecological differences reflecting a gradual adaptation to B eringian environments through time. Some methodological constraints associated with resolving recent (late Q uaternary) isolation events or drawing inferences from a single locus are discussed.

Niche differentiation and spatial partitioning in the evolution of two Australian monsoon tropical tree species - Robert D. Edwards; Michael D. Crisp; Lyn G. Cook (Journal of Biogeography, 2013)
Aim Geographical and climatic barriers to organismal dispersal and distribution play a major role in speciation. We use a sister‐pair of widespread savanna trees ( M elaleuca argentea and M . fluviatilis ) to test the influence of putative barriers on divergence within and between species across an otherwise continuous landscape. Location The A ustralian monsoon tropics ( AMT ). Methods Chloroplast and nuclear DNA sequences were used to estimate variation between and within species. Hypotheses invoking vicariance and ecological speciation as the mechanisms of divergence between species were explicitly tested using ecological niche modelling. Results We found little evidence for divergence across the C arpentaria B asin, although some chloroplast DNA haplotypes were restricted to regions to the east or west. Pilbara populations were distinct from those to the east across the Great Sandy Desert, including those from the Kimberley. There was a complex pattern of genetic divergence and niche differentiation among M . argentea and M . fluviatilis within a region of secondary range overlap coincident with currently recognized species boundaries across the Great Dividing Range. Main conclusions The two morphospecies are ecologically and genetically distinct, and maintain those differences in sympatry. Speciation might have occurred in allopatry in separate drainage basins that later came into contact. The P ilbara population appears to be distinct but requires further investigation.

A comparative gradient approach as a tool for understanding and managing urban ecosystems - Christopher G. Boone; Elizabeth Cook; Sharon J. Hall; Marcia L. Nation; Nancy B. Grimm; Carol B. Raish; Deborah M. Finch; Abigail M. York (Urban Ecosystems, 2012)

Holocene environmental change at Lake Shudu, Yunnan Province, southwestern China - Richard T. Jones; Charlotte G. Cook; Enlou Zhang; Peter G. Langdon; Jason Jordan; Chris Turney (Hydrobiologia, 2012)

Taxonomy and species boundaries in the coral genus Favia Milne Edwards and Haime, 1857 (Cnidaria: Scleractinia) from Thailand revealed by morphological and genetic data - N. Kongjandtre; T. Ridgway; L. G. Cook; T. Huelsken; A. F. Budd; O. Hoegh-Guldberg (Coral Reefs, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

GPS and time-depth loggers reveal underwater foraging plasticity in a flying diver, the Cape Cormorant - Timothée R. Cook; Maike Hamann; Lorien Pichegru; Francesco Bonadonna; David Grémillet; Peter G. Ryan (Marine Biology, 2012)

Sources and fate of nutrients in a subtropical reservoir - Michele A. Burford; Susanne A. Green; Andrew J. Cook; Suzanne A. Johnson; Jason G. Kerr; Katherine R. O’Brien (Aquatic Sciences, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Support for the ‘out-of-Southeast Asia’ hypothesis for the origin of Australian populations of Radopholus similis (Cobb, 1893) (Nematoda: Pratylenchidae) - Matthew Tan; Jennifer Cobon; Elizabeth Aitken; Lyn G. Cook (Systematic Parasitology, 2010)

Disturbance-mediated competition: the interacting roles of inundation regime and mechanical and herbicidal control in determining native and invasive plant abundance - Shon S. Schooler; Tony Cook; Graham Prichard; Alice G. Yeates (Biological Invasions, 2010)

Slowing of dexterous manipulation in old age: force and kinematic findings from the ‘nut-and-rod’ task - Kelly J. Cole; Kelly M. Cook; Stephanie M. Hynes; Warren G. Darling (Experimental Brain Research, 2010)

A mark-recapture population estimate for invasive silver carp (Hypophthalmichthys molitrix) in the La Grange Reach, Illinois River - Greg G. Sass; Thad R. Cook; Kevin S. Irons; Michael A. McClelland; Nerissa N. Michaels; T. Matthew O’Hara; Matthew R. Stroub (Biological Invasions, 2010)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

Phylogenetic endemism: a new approach for identifying geographical concentrations of evolutionary history - DAN ROSAUER; SHAWN W. LAFFAN; MICHAEL D. CRISP; STEPHEN C. DONNELLAN; LYN G. COOK (Molecular Ecology, 2009)
We present a new, broadly applicable measure of the spatial restriction of phylogenetic diversity, termed phylogenetic endemism (PE). PE combines the widely used phylogenetic diversity and weighted endemism measures to identify areas where substantial components of phylogenetic diversity are restricted. Such areas are likely to be of considerable importance for conservation. PE has a number of desirable properties not combined in previous approaches. It assesses endemism consistently, independent of taxonomic status or level, and independent of previously defined political or biological regions. The results can be directly compared between areas because they are based on equivalent spatial units. PE builds on previous phylogenetic analyses of endemism, but provides a more general solution for mapping endemism of lineages. We illustrate the broad applicability of PE using examples of Australian organisms having contrasting life histories: pea‐flowered shrubs of the genus Daviesia (Fabaceae) and the Australian species of the Australo‐Papuan tree frog radiation within the family Hylidae.

Convergence of tree water use within an arid-zone woodland - A. P. O’Grady; P. G. Cook; D. Eamus; A. Duguid; J. D. H. Wischusen; T. Fass; D. Worldege (Oecologia, 2009)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

Phylogenetic analysis of actinobacterial populations associated with Antarctic Dry Valley mineral soils - Olubukola O. Babalola; Bronwyn M. Kirby; Marilize Le Roes‐Hill; Andrew E. Cook; S. Craig Cary; Stephanie G. Burton; Don A. Cowan (Environmental Microbiology, 2009)
Summary Despite the apparent severity of the environmental conditions in the McMurdo Dry Valleys, Eastern Antarctica, recent phylogenetic studies conducted on mineral soil samples have revealed the presence of a wide diversity of microorganisms, with actinobacteria representing one of the largest phylotypic groups. Previous metagenomic studies have shown that the majority of Antarctic actinobacterial populations are classified as ‘uncultured’. In this study, we assessed the diversity of actinobacteria in Antarctic cold desert soils by complementing traditional culture‐based techniques with a metagenomic study. Phylogenetic analysis of clones generated with actinobacterium‐ and streptomycete‐specific PCR primers revealed that the majority of the phylotypes were most closely related to uncultured Pseudonocardia and Nocardioides species. Phylotypes most closely related to a number of rarer actinobacteria genera, including Geodermatophilus , Modestobacter and Sporichthya , were also identified. While complementary culture‐dependent studies isolated a number of Nocardia and Pseudonocardia species, the majority of the cultured isolates (> 80%) were S treptomyces species – although phylotypes affiliated to the genus Streptomyces were detected at a low frequency in the metagenomic study. This study confirms that Antarctic Dry Valley desert soil harbours highly diverse actinobacterial communities and suggests that many of the phylotypes identified may represent novel, uncultured species.

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

Another look at nagyágite from the type locality, S $\check{\rm{a}}$ c $\check{\rm{a}}$ rîmb, Romania: Replacement, chemical variation and petrogenetic implications - C. L. Ciobanu; N. J. Cook; A. Pring; G. Damian; N. Căpraru (Mineralogy and Petrology, 2008)

Transcriptome Analyses of Amoebic Gill Disease-affected Atlantic Salmon (Salmo salar) Tissues Reveal Localized Host Gene Suppression - James W. Wynne; Maree G. O’Sullivan; Mathew T. Cook; Glenn Stone; Barbara F. Nowak; David R. Lovell; Nicholas G. Elliott (Marine Biotechnology, 2008)

Andropogon gayanus (Gamba Grass) Invasion Increases Fire-mediated Nitrogen Losses in the Tropical Savannas of Northern Australia - N. A. Rossiter-Rachor; S. A. Setterfield; M. M. Douglas; L. B. Hutley; G. D. Cook (Ecosystems, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

Comparative phylogeography and demographic history of the wood lemming ( Myopus schisticolor ): implications for late Quaternary history of the taiga species in Eurasia - V. B. FEDOROV; A. V. GOROPASHNAYA; G. G. BOESKOROV; J. A. COOK (Molecular Ecology, 2008)
The association between demographic history, genealogy and geographical distribution of mitochondrial DNA cytochrome b haplotypes was studied in the wood lemming ( Myopus schisticolor ), a species that is closely associated with the boreal forest of the Eurasian taiga zone from Scandinavia to the Pacific coast. Except for a major phylogeographic discontinuity (0.9% nucleotide divergence) in southeastern Siberia, only shallow regional genetic structure was detected across northern Eurasia. Genetic signs of demographic expansions imply that successive range contractions and expansions on different spatial scales represented the primary historical events that shaped geographical patterns of genetic variation. Comparison of phylogeographic structure across a taxonomically diverse array of other species that are ecologically associated with the taiga forest revealed similar patterns and identified two general aspects. First, the major south–north phylogeographic discontinuity observed in five out of six species studied in southeastern Siberia and the Far East implies vicariant separation in two different refugial areas. The limited distribution range of the southeastern lineages provides no evidence of the importance of the putative southeastern refugial area for postglacial colonization of northern Eurasia by boreal forest species. Second, the lack of phylogeographic structure associated with significant reciprocal monophyly and genetic signatures of demographic expansion in all nine boreal forest animal species studied to date across most of northern Eurasia imply contraction of each species to a single refugial area during the late Pleistocene followed by range expansion on a continental scale. Similar phylogeographic patterns observed in this taxonomically diverse set of organisms with different life histories and dispersal potentials reflect the historical dynamics of their shared environment, the taiga forest in northern Eurasia.

Impact of canal development on intertidal microalgal productivity: Comparative assessment of Patterson Lakes and Ralphs Bay, South East Australia - S. S. Cook; J. L. Roberts; G. M. Hallegraeff; A. McMinn (Journal of Coastal Conservation, 2007)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Deliberate omission or unfortunate oversight: Should stygofaunal surveys be included in routine groundwater monitoring programs? - Moya Tomlinson; Andrew J. Boulton; Peter J. Hancock; Peter G. Cook (Hydrogeology Journal, 2007)

Neurobehavioral mutants identified in an ENU-mutagenesis project - Melloni N. Cook; Jonathan P. Dunning; Ronald G. Wiley; Elissa J. Chesler; Dabney K. Johnson; Darla R. Miller; Dan Goldowitz (Mammalian Genome, 2007)

Isolation of viral haemorrhagic septicaemia virus from mummichog, stickleback, striped bass and brown trout in eastern Canada - N Gagné; A‐M MacKinnon; L Boston; B Souter; M Cook‐Versloot; S Griffiths; G Olivier (Journal of Fish Diseases, 2007)
Viral haemorrhagic septicaemia virus (VHSV) was isolated from mortalities occurring in populations of mummichog, Fundulus heteroclitus , stickleback, Gasterosteus aculeatus aculeatus , brown trout, Salmo trutta , and striped bass, Morone saxatilis , in New Brunswick and Nova Scotia, Canada. The isolated viral strains produced a cytopathic effect on the epithelioma papillosum cyprini cell line. Serum neutralization indicated the virus was VHSV and sequencing identified the rhabdovirus isolates as the North American strain of VHSV. Phylogenetic analysis indicated that the isolates are closely related and form a distinguishable subgroup of North American type VHSV. To our knowledge, this is the first report of VHSV in mummichog and striped bass.

Allelic and haplotypic diversity at the major histocompatibility class II within domesticated Australian Atlantic salmon ( Salmo salar L.) - J. W. Wynne; M. T. Cook; B. H. Holmes; N. G. Elliott (Journal of Fish Biology, 2007)
Variation within the major histocompatibility (MH) class II alpha gene ( Sasa‐DAA ) was compared between domesticated Australian Atlantic salmon and their ancestral Canadian population. The level of Sasa‐DAA and MH class II beta gene ( Sasa‐DAB ) sequence variation was also examined within the Australian population and compared with that published for European Atlantic salmon populations. In contrast to variation previously reported for non‐coding microsatellite loci, a high level of MH class II allelic variation has been maintained within the domesticated Australian populations. Furthermore, a high level of Sasa‐DAA and Sasa‐DAB allele sequence diversity was also observed and exceeded that reported for other cultured Atlantic salmon populations. The number of Sasa‐DAB allele sequences (14) surpassed the number of Sasa‐DAA allele sequences (9) to produce 14 unique class II haplotypes. We conclude that the Australian Atlantic salmon populations show high MH class II allelic and haplotypic variation compared with both its ancestral Canadian population and other cultured Atlantic salmon populations.

Thermal tolerance of a northern population of striped bass Morone saxatilis - A. M. Cook; J. Duston; R. G. Bradford (Journal of Fish Biology, 2006)
Thermal tolerance of age 0+ year Shubenacadie River (Nova Scotia, Canada) striped bass Morone saxatilis juveniles (mean ± s . e . fork length, L F , 19·2 ± 0·2 cm) acclimated in fresh water to six temperatures from 5 to 30° C was measured by both the incipient lethal technique (72 h assay), and the critical thermal method ( C m ). The lower incipient lethal temperature ranged from 2·4 to 11·3° C, and the upper incipient lethal temperature ( I U ) from 24·4 to 33·9° C. The area of thermal tolerance was 618° C 2 . In a separate experiment, the I U of large age 2+ year fish (34·4 ± 0·5 cm L F ) was 1·2 and 0·6° C lower ( P L F ) at acclimation temperatures of 16 and 23° C. Using the C m , loss of equilibrium occurred at 27·4–37·7° C, loss of righting response at 28·1–38·4° C and onset of spasms at 28·5–38·8° C, depending on acclimation temperature. The linear regression slopes for these three responses were statistically similar (0·41; P > 0·05), but the intercepts differed (25·3, 26·0 and 26·5° C; P

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Preface – Special Issue: Telluride and selenide minerals in gold deposits – how and why? - C. L. Ciobanu; N. J. Cook; P. G. Spry (Mineralogy and Petrology, 2006)

Gold scavenged by bismuth melts: An example from Alpine shear-remobilizates in the Highiş Massif, Romania - C. L. Ciobanu; N. J. Cook; F. Damian; G. Damian (Mineralogy and Petrology, 2006)

Determining soil and ground water use of vegetation from heat pulse, water potential and stable isotope data - P. G. Cook; A. P. O’Grady (Oecologia, 2006)

Bactericidal effects of plasma-generated cluster ions - I. Digel; A. Temiz Artmann; K. Nishikawa; M. Cook; E. Kurulgan; G. M. Artmann (Medical & Biological Engineering & Computing, 2005)

Directional asymmetry of long‐distance dispersal and colonization could mislead reconstructions of biogeography - Lyn G. Cook; Michael D. Crisp (Journal of Biogeography, 2005)
Aim Phylogenies are increasingly being used to attempt to answer biogeographical questions. However, a reliance on tree topology alone has emerged without consideration of earth processes or the biology of the organisms in question. Most ancestral‐state optimization methods have inherent problems, including failure to take account of asymmetry, such as unequal probabilities of losses and gains, and the lack of use of independent cost estimates. Here we discuss what we perceive as shortcomings in most current tree‐based biogeography interpretation methods and show that consideration of processes and their likelihoods can turn the conventional biogeographical interpretation on its head. Location Southern hemisphere focus but applicable world‐wide. Methods The logic of existing methods is reviewed with respect to their adequacy in modelling processes such as geographical mode of speciation and likelihood of dispersal, including directional bias. Published reconstructions of dispersal of three plant taxa between Australia and New Zealand were re‐analysed using standard parsimony and maximum likelihood (ML) methods with rate matrices to model expected asymmetry of dispersal. Results Few studies to date incorporate asymmetric dispersal rate matrices or question the simplistic assumption of equal costs. Even when they do, cost matrices typically are not derived independently of tree topology. Asymmetrical dispersal between Australia and New Zealand could be reconstructed using parsimony but not with ML. Main conclusions The inadequacy of current models has important consequences for our interpretation of southern hemisphere biogeography, particularly in relation to dispersal. For example, if repeated directional dispersals and colonization in the direction of prevailing winds have occurred, with intervening periods of speciation, then there is no need to infer dispersals against those winds. Failure to take account of directionality and other biases in reconstruction methods has implications beyond the simple misinterpretation of the biogeography of a taxonomic group, such as calibration of molecular clocks, the dating of vicariance events, and the prioritization of areas for conservation.

Cotton rat Sihi- M3 is a minimally oligomorphic Mhc I-b molecule that binds the chemotactic peptide fMLF under stringent conditions - C. Kuyler Doyle; Richard G. Cook; Robert R. Rich; John R. Rodgers (Immunogenetics, 2003)

Nitrous oxide emissions following application of residues and fertiliser under zero and conventional tillage - E.M. Baggs; M. Stevenson; M. Pihlatie; A. Regar; H. Cook; G. Cadisch (Plant and Soil, 2003)

Using groundwater levels to estimate recharge - Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Choosing appropriate techniques for quantifying groundwater recharge - Bridget R. Scanlon; Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Theme issue on groundwater recharge - Bridget R. Scanlon; Peter G. Cook (Hydrogeology Journal, 2002)

Spatial variation in the duration of the rainy season in monsoonal Australia - Garry D. Cook; Richard G. Heerdegen (International Journal of Climatology, 2001)
Climatological research in the tropics of northern Australia has focused particularly on the Australian summer monsoon. However, the timing of many ecologically important processes is determined not by the monsoon but by extra‐monsoonal rainfall events. These events produce a temporal pattern of wet and dry spells that is at least as important ecologically as the amount of rain. We defined the rainy season as that period when the probability of 10‐day dry spells was less than 0.5, and the wet season as that period within the rainy season when the probability of dry spells was less than 0.1. We applied these criteria to seven stations along a strong north–south rainfall gradient spanning more than 12° of latitude in tropical north Australia. The duration of the rainy and wet seasons in northern Australia decreases with increasing latitude. The timing and duration of these seasons were also affected by the El Niño–Southern Oscillation (ENSO). The relative contribution of temporally isolated rainfall events to both the duration of the rainy season and the amount of rainfall increases with latitude. The geographic variation in these seasons corresponds to many patterns occurring in natural ecosystems. We argue that understanding the extra‐monsoon rainfall events is critical to understanding how climate variation affects natural ecosystems. Copyright © 2001 Royal Meteorological Society

Identification and Characterization of Segments 3 and 4 of the ISAV Genome - Rachael J. Ritchie; Joël Heppell; Marcia B. Cook; Simon Jones; Steve G. Griffiths (Virus Genes, 2001)

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Cloning and sequence analysis of the H2-K2 b gene reveals that it is a pseudogene - Rajneesh P. Uzgare; R. G. Cook (Immunogenetics, 1999)

Sex allocation and local mate competition in Old World non-pollinating fig wasps - Mark D. E. Fellowes; Steve G. Compton; James M. Cook (Behavioral Ecology and Sociobiology, 1999)

Construction of a bacterial artificial chromosome library of Medicago truncatula and identification of clones containing ethylene-response genes - Y.-W. Nam; R. V. Penmetsa; G. Endre; P. Uribe; D. Kim; D. R. Cook (Theoretical and Applied Genetics, 1999)

Mineralogy and textural relationships among sulphosalts and related minerals in the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - N. J. Cook; P. G. Spry; F. M. Vokes (Mineralium Deposita, 1998)

Thermobarometry of the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - J. L. Rosenberg; P. G. Spry; C. E. Jacobson; N. J. Cook; F. M. Vokes (Mineralium Deposita, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Evidence of deep circulation in two perennially ice‐covered Antarctic lakes - Scott W. Tyler; Peter G. Cook; Anya Z. Butt; James M. Thomas; Peter T. Doran; W. Berry Lyons (Limnology and Oceanography, 1998)
The perennial ice covers found on many of the lakes in the McMurdo Dry Valley region of the Antarctic have been postulated to severely limit mixing and convective turnover of these unique lakes. In this work, we utilize chlorofluorocarbon (CFC) concentration profiles from Lakes Hoare and Fryxell in the McMurdo Dry Valley to determine the extent of deep vertical mixing occurring over the last 50 years. Near the ice‐water interface, CFC concentrations in both lakes were well above saturation, in accordance with atmospheric gas supersaturations resulting from freezing under the perennial ice covers. Evidence of mixing throughout the water column at Lake Hoare was confirmed by the presence of CFCs throughout the water column and suggests vertical mixing times of 20–30 years. In Lake Fryxell, CFC‐11, CFC‐12, and CFC‐113 were found in the upper water column; however, degradation of CFC‐ 11 and CFC‐ 12 in the anoxic bottom waters appears to be occurring with CFC‐ 113 only present in these bottom waters. The presence of CFC‐113 in the bottom waters, in conjunction with previous work detecting tritium in these waters, strongly argues for the presence of convective mixing in Lake Fryxell. The evidence for deep mixing in these lakes may be an important, yet overlooked, phenomenon in the limnology of perennially icecovered lakes.

Homology modelling of the catalytic domain of early mammalian protein C: evolution of structural features - A. I. Wacey; M. Krawczak; G. Kemball-Cook; D. N. Cooper (Human Genetics, 1997)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Limb regeneration and subsequent asymmetry in a male secondary sexual character influences sexual selection in wolf spiders - G. W. Uetz; William J. McClintock; Douglas Miller; Elizabeth I. Smith; Kristina K. Cook (Behavioral Ecology and Sociobiology, 1996)

Effects of risks of sperm competition on the numbers of eupyrene and apyrene sperm ejaculated by the moth Plodia interpunctella (Lepidoptera: Pyralidae) - P. A. Cook; Matthew J. G. Gage (Behavioral Ecology and Sociobiology, 1995)

Effects of risks of sperm competition on the numbers of eupyrene and apyrene sperm ejaculated by the moth Plodia interpunctella (Lepidoptera: Pyralidae) - Penny A. Cook; Matthew J. G. Gage (Behavioral Ecology and Sociobiology, 1995)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

Respiratory nitrate reduction by Desulfovibrio sp. - R. G. L. McCready; W. D. Gould; F. D. Cook (Archives of Microbiology, 1983)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Metabolite concentrations in Alcaligenes eutrophus H 16 and a mutant defective in poly-?-hydroxybutyrate synthesis - Alasdair M. Cook; Hans G. Schlegel (Archives of Microbiology, 1978)

Evidence for the in vivo regulation of glucose 6-phosphate dehydrogenase activity in Hydrogenomonas eutropha H 16 from measurements of the intracellular concentrations of metabolic intermediates - B. Bowien; A. M. Cook; H. G. Schlegel (Archives of Microbiology, 1974)

The severity of potato scab in relation to the use of neutralized and one-third neutralized fertilizers - Harold T. Cook; G. V. C. Houghland (American Journal of Potato Research, 1942)